INDUSTRIAL CROP AS ONE OF THE SOURCES OF REVENUE OF PEOPLE OF SUBMONTANE AND PLAIN DAGESTAN - Aliev, B G (History, Archeology and Ethnography of the Caucasus, 2015)
Basing on the available sources and literature the author makes the first attempt to show the state of development in Dagestan of such industrial crops as madder, cotton, saffron, silk, tobacco, hemp. The article presents the areas of their distribution and their importance for the economic life of the population of plain and submontane Dagestan. The data on madder trade, which forced out grain production in some regions of Dagestan and brought large income to its producers, are of special interest.
Keywords: madder-raising; cotton-raising; silk-raising; saffron; tobacco growing; hemp; Derbent; Kaitag; Tabasaran; Trans-Sulak Kumykiya